Accuracy of 128-slice multi-detector computed tomography in the detection of stenosis at different cut-off values in corresponding target areas on conventional angiogram - Zaman, Farhana; Khan, M. Javed Mahfuz; Chowdhury, Abdulla Al Mahaj (International Surgery Journal, 2024)
Background: Coronary artery disease (CAD) is a common medical condition. Over the years, assessment methods for CAD have evolved, with non-invasive techniques gaining prominence. Multi-detector computed tomography (MDCT) coronary angiography has emerged as an alternative to conventional invasive coronary angiography (ICA). This study aimed to evaluate the diagnostic accuracy of 128-slice MDCT in detecting stenosis at various thresholds and compare its efficacy with traditional coronary angiography. Methods: This cross-sectional study was conducted at the radiology and imaging department of combined military hospital (CMH) in Dhaka from August 2021 to July 2022. Forty-three patients were selected through purposive sampling. Computed tomographic angiography was performed using a 128-slice MDCT scanner. Data analysis was conducted using SPSS, with statistical significance set at p<0.05. Sensitivity, specificity, diagnostic accuracy, negative predictive value (NPV), and positive predictive value (PPV) were calculated for each patient and segment. Sensitivity and specificity were assessed for stenosis exceeding 75% and 50%. Result: For diagnosing stenosis less than 50%, the sensitivity, specificity, PPV, NPV, and accuracy were 83.9%, 95.6%, 61.0%, 98.6%, and 94.7%, respectively. For stenosis greater than 50%, they were 84.2%, 99.3%, 86.5%, 99.1%, and 98.5%. For stenosis exceeding 75%, the values were 100.0%, 99.9%, 97.0%, 100.0%, and 99.9%. Conclusions: 128-slice CT provides a reliable non-invasive method to assess hemodynamically significant CAD with high diagnostic accuracy. The study findings suggest that at the artery level, MDCT demonstrates high level of accuracy in identifying significant obstructive CAD.